Peran Pemerintah di Bidang Perekonomian Dalam Islam - Hidayatullah, Indra (Dinar : Jurnal Ekonomi dan Keuangan Islam, 2015)
Abstract Government is the authorized party in making and applying basic rules to support and protect economic activities and improvement. In the structure of a society, the role and responsibility of government is an inseparable part in creating an order and prosperous society. On the prospective of Islam, government’s responsibility is relatively flexible based on the premise that Islam aims to create prosperity for public.Among some of government’s important tasks in the economic sector are to examine and control the main driving factors in mobilizing the economy, stop any forbidden transaction and regulate the standard price when it is needed. Control and intervention of government are conducted through some ways. Some of which are regulation prohibiting the transaction of forbidden or restricted products, regulation prohibiting any type and form of manipulation in the whole economic activity, regulation prohibiting the distribution of healthy-endangering food, drink and other products, regulation prohibiting any game related to interest and property of people at general, regulation prohibiting works in any forbidden sector and regulation limiting production of commodity which is not the main need of people. Keywords: monitoring, intervention, role of government AbstrakNegara merupakan pihak yang memiliki kewenangan dalam meletakkan dasar-dasar aturan yang mendukung dan dapat melindungi pertumbuhan  dan aktifitas ekonomi. Dalam kehidupan masyarakat tidak dapat dilepaskan dari tanggung jawab pemerintah yang berusaha melakukan penertiban dan mensejahterakan masyarakat. Tanggung jawab pemerintah dalam persepektif  Islam memiliki fleksibilitas yang luas didasarkan pada premis bahwa islam bertujuan untuk mensejahterakan umum masyarakat.Di antara tugas-tugas penting pemerintah dalam perekonomian adalah mengawasi faktor utama penggerak perekonomian, menghentikan muamalah yang diharamkan, dan mematok harga kalau dibutuhkan. Pengawasan dan intervensi yang dilakukan oleh pemerintah tersebut dapat melalui beberapa hal, di antaranya adalah Regulasi yang melarang jual beli barang yang diharamkan, regulasi yang melarang semua bentuk dan jenis manipulasi dalam semua aktivitas ekonomi, regulasi yang melarang peredaran makanan, minuman atau bahan lainnya yang membahayakan kesehatan umum, regulasi yang melarang permainan terhadap kepentingan dan harta manusia secara umum, regulasi yang melarang pekerjaan sektor-sektor yang diharamkan, dan regulasi yang membatasi produksi komoditi yang tidak terlalu dibutuhkan masyarakat.Keywords : pengawasan, intervensi, peran pemerintah.